The Process of Spiritual Care - Nissen, Ricko Damberg; Viftrup, Dorte Toudal; Hvidt, Niels Christian (Frontiers in Psychology, 2021)
The aim of this article is to illustrate and outline an understanding of spiritual care as a process involving a number of organically linked phases: 1. the identification of spiritual needs and resources, 2. understanding the patient’s specific needs, 3. developing the individual spiritual care treatment plan, hereunder involving the relevant healthcare/spiritual care professionals, 4. the provision of spiritual care, and 5. evaluating the spiritual care provided. The focus on spiritual care in healthcare research has increased throughout the past decades, showing that existential, spiritual, and/or religious considerations and needs increase with life-threatening illness, that these needs intensify with the severity of disease and with the prospect of death. Furthermore, research has shown that spiritual care increases quality of life, but also that failing to provide spiritual care leads to increased chance of depression and lowered health conditions. The World Health Organization accordingly emphasizes that providing spiritual care is vital for enhancing quality-of-life. Looking at spiritual care as a process suggests that working within a defined conceptual framework for providing spiritual care, is a recommendable default position for any institution where spiritual care is part of the daily work and routines. This so, especially because looking at spiritual care as a process highlights that moving from identifying spiritual needs in a patient to the actual provision of spiritual care, involves deliberate and considered actions and interventions that take into account the specific cultural and ontological position of the patient as well as the appropriate persons to provide the spiritual care. By presenting spiritual care as a process, we hope to inspire and to contribute to the international development of spiritual care, by enabling sharing experiences and best-practices internationally and cross-culturally. This so to better approach the practical and daily dimensions of spiritual care, to better address and consider the individual patient’s specific spiritual needs, be they secular, spiritual and /or religious. In the final instance, spiritual care has only one ambition; to help the individual human being through crisis.